KETERKAITAN CUACA DI INDONESIA DENGAN FENOMENA BINTIK MATAHARI (SUNSPOT)(RELATIONSHIP BETWEEN WEATHER IN INDONESIA AND SUNSPOT PHENOMENON) - B. Basyaruddin; S. Effendy (Agromet, 2007)
The Sun activity was correlation with weather activities in global scale. Shortwave emission from flare sun space could be impact warmer in earth atmosphere only a short time and indirect caused atmospheric circulation pattern through polar direction from equator with more heater than the other palaces. Based on research the sun activity can caused indirect on the earth. On the other hand, atmosphere is in the first time accept effect modify from sun space. The effect is not the same at every layers of atmosphere. In the top atmosphere (Ionosphere) was layer with more free electron at the 225 km level occurred electron density diurnal and seasonal variation depend on sun position, and sun spot cycle. Sun spot impact on Indonesian weather with non-linier cubic equation. Solar radiation higher if increase amount of sun spot in the sun space. On the other hand, temperature and relative humidity influenced by outgoing radiation from earth, latitude and local topography specific than sunspot. It is interesting to note that this study different with literature. This study found average temperature in the tropic area the most highest than others area is contrary with literature.